The role of media for consumers' inflation expectation formation - Michael J. Lamla; Sarah M. Lein (ETH Zurich, KOF Swiss Economic Institute, 2008)
This paper analyzes the impact of the media on consumers' inflation expectations. We distinguish two channels through which media can influence expectations. First, the intensity of news coverage on inflation plays a role (volume channel). Second, the content of these reports matters (tone channel). Employing a unique data set capturing media reports on inflation in Germany comprising 01/1998-12/2006 we are able to discriminate between these two effects. We find that the volume effect generally improves the accuracy of consumer forecasts while the tone channel induces a media bias.
Keywords: E52; D83; 330; Monetary policy; expectation formation; media coverage; media bias; Inflationserwartung; Medienverhalten; Informationsbeschaffung; Bias; Deutschland